Analisa Pengendalian Kualitas Produk Tauge Dengan Metode Six Sigma Di CV. Berkah Kecambah Tauge Aling - Yahya Aji Setiawan; Ari Zaqi Alfaritsy (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2023)
CV Berkah Kecambah Tauge Aling is a company engaged in the field of food or vegetable bean sprouts made from green beans. In the production of CV Berkah Kecambah Tauge Aling there was a product defect in January 2023 which occurred, namely the result of the defect rate which was known to have the highest number of defects in the yellow color defect of 1818 packages, with a defect percentage of 58.3%. Then the Bad Smell defects with a total of 879 defects, a percentage of defects obtained by 28.2%, the type of defective packaging torn with a total of 423 defects, a percentage of defects of 13.6%. it is known that the diagram (p-chart) with the type of product defect still has 13 points exceeding the upper control limit or UCL and there are 12 points exceeding the lower control limit or LCL with a proportion of 0.148. Judging from the results of DPMO calculations and Sigma Levels, an average DPMO of 49619 is obtained, so that if there is a product defect of 49619 out of 1,000,000 opportunities in the Sprouts production process at CV. The Blessing of Aling Bean Sprouts. In the FMEA diagram to find out the factors and RPN values that result in product defects including human factors, machines, materials, methods, and the environment, the results of the FMEA analysis cause the biggest defects, namely yellowing defects with an RPN value of 810.